ANALISIS MAQASHID ASY-SYARIAH DALAM PENGELOLAAN ZAKAT OLEH NEGARA - Hani Fauziah; Didin Hafidhuddin; Hendri Tanjung (Univ Ibn Khaldun Bogor, 2019)
Aim of this research is to explore extent which relationship between state and zakah in realizing ideals of zakah legal Islamic low. Examined from al-maqashid ash-sharia, jurisprudence, historical, and application in three countries, in order to search for a formula that is most conducive to optimizing the role of zakah. This research use qualitative methods. Begin extracting the information of zakah payment pattern in society, involving 200 respondents randomly which is then combined with a literature study of the book of previous scholars, contemporary, and fatwa. The research also parses comparison zakah management in three countries that run through the zakah management system of the country, namely Brunei Darussalam, Malaysia, and Pakistan. Results of research revealed that zakah can be explored optimally if supported by active role of the State and its rules that support the passage whole system of zakat. To realizing al-maqashid ash- shariah, so zakah should not be separated from the institutional context. Over the leader of a Muslim country still distribute zakat to needy people, and then zakah management that is integrated into state system will bring mashlahah more for people than separate managing.